Climatic variability and its role in regulating C, N and P retention in the James River Estuary. (31st May 2018) - Bukaveckas, Paul A.; Beck, Michael; Devore, Dana; Lee, William M.
Abstract: Transformations and retention of C, N and P inputs to estuaries are subject to external factors such as discharge-driven variation in loading rates, and internal processes regulating biogeochemical cycles. We used an 8-year time series of finely resolved (monthly) mass balances for the tidal freshwater segment of the James River Estuary to assess the influence of discharge and temperature on C, N and P retention. Peak export and retention of organic, likely particulate, fractions occurred in months of highest discharge. With increasing discharge we observed higher mass retention, greater proportional retention (in relation to inputs) and more selective retention (with P retained preferentially over N and C). DIN retention was strongly influenced by water temperature with 10-fold high retention occurring at high (>20 °C) vs. low (<15 °C) water temperature at corresponding discharge. Our findings suggest that rising temperatures will have a greater effect on the retention of N than P because a greater proportion of the total N delivered to estuaries is in dissolved inorganic form, and therefore subject to temperature dependent rates of biological assimilation and denitrification. By contrast, the bulk of the P load was in particulate form, which is retained via sediment trapping, and not appreciably affected by water temperature. The tidal freshwater estuary was an important site for nutrient removal where the accumulation of N- and P- rich materials may delay recovery in response to nutrient load reductions.